Pendidikan Perkoperasian Mengenai Prinsip dan Akad Serta Produk Koperasi Syariah untuk Pengelola dan Anggota Koperasi Syariah Al-Muhajir Bandung - Nanang Sobarna (E-Coops-Day, 2023)
The development of Islamic Cooperatives is inseparable from the process of cooperative education as a means to increase the understanding of managers in order to be able to manage Islamic cooperatives that really lead to the general goal of establishing cooperatives, namely to realize prosperity for members and the community and to be able to carry out Islamic cooperative operations in accordance with Islamic principles. The aim of this sharia cooperative education is to understand managers so that they can run sharia cooperative operations in accordance with sharia principles and increase member participation in utilizing Sharia Cooperative products. The method used in cooperative education is the lecture method, assisted by visual displays of the material presented in order to provide a clear and complete understanding of the principles, contracts, and products of sharia cooperatives. Then it is followed by questions and answers and discussion regarding the application of sharia cooperative principles, contracts, and products as well as problems and solutions that can be implemented in order to solve problems that arise. Through the implementationof this cooperative education, managers and members of the Al-Muhajir Sharia Cooperative have been able to understand what principles must be built in running sharia cooperatives. As well as managers and members of the Al-Muhajir Sharia Cooperative are also able to understand Sharia Cooperative contracts and products such as contracts and Savings products Wadhi'ah, Savings Mudharabah, business financing, financing of the purchase of goods, and rental contracts.